Birth asphyxia, determinants, and its management among neonates admitted to NICU in Harari and Dire Dawa Public Hospitals, eastern Ethiopia - Amsalu, Sewmehon; Dheresa, Merga; Dessie, Yadeta; Eshetu, Bajrond; Balis, Bikila (Frontiers in Pediatrics, 2023)
Background: Despite a declining neonatal mortality rate across the globe, Ethiopia has scored 29 to 30 deaths per 1,000 live births. Birth asphyxia has major contribution for the neonatal mortality where four to nine million newborns develop birth asphyxia each year. This study aimed to assess the prevalence of birth asphyxia, determinants and its managements among neonates admitted to NICU in Harari and Dire Dawa public hospitals. Methods: A facility-based cross-sectional study was conducted among 409 randomly selected neonates and their index mother admitted to neonatal intensive care unit of selected public hospitals in Harari and Dire Dawa from June 20 to August 20, 202. Data were collected through card review and interviewer-administered questionnaire. The collected data were entered into Epi data version 3.1 and exported to SPSS version 20 for analysis. Logistic regression models were fitted to identify factors associated with birth asphyxia. Adjusted odds ratios along with 95% CI were estimated to measure the strength of the association, and statistical significance was declared at a p-value < 0.05. Results: One-fifth of neonates, (20.8% (95% CI: 16.4, 24.6%)) had birth asphyxia. Neonates born by instrumental delivery (AOR=2.29, 95% CI: 1.10, 4.76), neonate born to mother with PIH (AOR=3.49, 95% CI: 1.47, 8.27), PROM (AOR=2.23, 95% CI: 1.17, 4.26) and Chorioamnionitis (AOR=3.26, 95% CI: 1.10, 9.61) were more likely had birth asphyxia compared to their counterpart. Conclusion: One out of five neonates had birth asphyxia. This urges care providers to adhere national guidelines of obstetrics and neonatal continuum care. Also, averting birth asphyxia necessitates decreasing instrumental delivery rate, and treating PIH, PROM and Chorioamnionitis.